INTEGRATION OF SCHOOL HEALTH BUSINESS TRIAS AND ADIWIYATA PROGRAM TO REALIZE ENVIRONMENTALLY FRIENDLY SCHOOLS (CASE STUDIES IN SCHOOLS BANGKALA DISTRICT, JENEPONTO REGENCY) - Sahabuddin, Erma Suryani; Idrus, Nur Abidah; Amrah, Amrah; Putrawan, Muh Rizah; Anggraeni K, Dwi Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study uses a qualitative descriptive method to describe and interpret the Analysis of the Implementation of the School Health Triad (UKS) and Adiwiyata in five elementary schools in Bangkala District, Jeneponto Regency. The purposive sampling method was used to select schools, and data was collected through semi-structured interviews, observations, and documentation. This research focuses on the evaluation of the implementation and Adiwiyata based on the participation of students, parents, health agencies, teachers, and school staff. The results show that although efforts have been made, the implementation has not been optimal due to constraints such as lack of space facilities and lack of health education. Health services are still limited to activities from the health center without the active involvement of teachers. Meanwhile, the Adiwiyata program has not been fully integrated into the curriculum, but reforestation activities have been carried out with the participation of school residents and the local government. Data analysis uses qualitative descriptive techniques that include data reduction, data presentation, and conclusion drawn, by ensuring the validity of the data through triangulation methods. This study concludes that efforts for the implementation of UKS and Adiwiyata have been made, but it is still necessary to solve several obstacles to improve health and the environment in schools, such as the separation of the UKS room from other rooms is needed to be more effective, training and coaching for Supervisors is also important so that in the implementation of health counseling, the involvement of the health center is not always needed, in addition, The school is expected to become an Adiwiyata school, because the implementation is almost similar